Significant effects of RNAi silencing of the venom allergen‐like protein (Mhi‐vap‐1) of the root‐knot nematode Meloidogyne hispanica in the early events of infection. (6th February 2017) - Duarte, A.; Maleita, C.; Egas, C.; Abrantes, I.; Curtis, R.
Abstract : Gene silencing using RNAi is a powerful tool for functional analysis of nematode genes and can provide a new strategy for the management of root‐knot nematodes. The transcript of the venom allergen‐like protein gene ( Mhi‐vap‐1 ) of Meloidogyne hispanica is localized in the subventral oesophageal gland cells of second‐stage juveniles (J2) and the gene is highly transcribed in this developmental nematode stage. The purpose of this study was to assess whether the silencing of the Mhi‐vap‐1 gene could affect nematode attraction to roots, penetration, development and reproduction in tomato plants. The optimum soaking time to generate silencing of this gene was determined by quantitative RT‐PCR analysis of the relative expression of the Mhi‐vap‐1 gene in the J2 incubated with the soaking solution for 24, 32 and 48 h. At 48 h, the relative expression of Mhi‐vap‐1 decreased, which indicates that this period of time is optimum to silence this nematode gene using the RNAi method. Silencing of the Mhi‐vap‐1 gene interfered with the completion of the nematode life cycle and caused a reduction in nematode attraction to roots, penetration and infection of plants. A small difference in the number of females and galls formed was also observed, which caused a small decrease in the nematode reproduction factor. The use of RNAi silencing of the Meloidogyne effector gene Mhi‐vap‐1 showed that this gene is important for the plant–nematode interaction during the early events of infection and could be a target gene for anti‐nematode strategies.